Continuities and discontinuities in pharmaceutical treatment and medication use among older chronically ill patients of Turkish descent in Germany: a qualitative structuring content analysis - Tezcan-Güntekin, Hürrem; Bird, Rona; Aslan, Sema; Kul, Yagmur; Azman, Özge; Aykaç, Volkan; Klammt, Beate; Aslan, Meryem; Özer-Erdoğdu, Ilknur (Frontiers in Public Health, 2024)
Background Polypharmacy occurs frequently among older adults and is associated with an increased risk of falls and medication-related adverse events. In particular, people with a history of migration may receive inappropriate medication due to language barriers or discrimination in healthcare. This study aims to assess the continuities, discontinuities and barriers to drug therapy in older migrants of Turkish descent in Berlin, Germany. Methods Eleven problem-centered qualitative interviews with chronically ill older persons of Turkish descent and family caregivers were conducted and analyzed qualitatively by means of structuring content analysis. Results The chronically ill participants of Turkish descent predominantly take more than 5 types of medication per day and aim to take them regularly. Discontinuities emerge when medication is forgotten or intentionally omitted due to side effects. Frequent changes in medication and physicians' lack of time are relevant barriers to drug treatment plans. To avoid language barriers and disinterest on the part of professionals, respondents prefer Turkish-speaking physicians.